Elimination of loop-check for logic of idealized knowledge - Pliuškevičienė, Aida (Lietuvos matematikos rinkinys, 2009)
In the paper loop-check-free sequent calculus for logic of idealized knowledge is presented. To obtain termination of derivation indices and marks are used instead of history.
Keywords: modal logics; sequent calculus; termination of derivation; loop-check; indexation